Effects of Increasing Laser Power on Microstructure Formed During Selective Laser Melting of Co-29Cr-6Mo Alloy - Darvish, Kourosh (Auckland University of Technology, 2018)
For a wider medical/dental and aerospace applications of 3D printed parts made using selective laser melting (SLM) Co-29Cr-6Mo alloy, how SLM parameters affect the quality and properties of parts need to be understood. In this PhD research, how laser power (P) affects the geometry of tracks was studied first. This track geometry relates well to a major defect, lack of fusion (LOF), which affects part quality. Through examining extensively the track profiles, the effect of P on the amount of LOF has been found and has been geometrically explained. Furthermore, we have identified an abnormal type of LOF caused by spatters and how melt penetration may reduce this type of LOF has also been shown. The second and major part of this thesis was to study how the tiny melt rapidly solidifies during SLM, as it is well known that solidification microstructure directly relates to properties of the parts. Cellular solidification without a planar layer has been observed and explained based on constitutional supercooling. Growth direction selection during epitaxial growth has been identified and explained considering local heat flux direction. Finally, cell size measurement and growth rate estimation have enabled the calculation of thermal quantities during SLM solidification.
Keywords: Selective laser melting; 3D printing; Co-29Cr-6Mo; Lack of fusion; Solidification